2021
DOI: 10.1016/j.jamda.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Muscle Mass, Muscle Strength, and Physical Performance in Acutely Hospitalized Older Adults

Abstract: Objectives: Acute hospitalization may lead to a decrease in muscle measures, but limited studies are reporting on the changes after discharge. The aim of this study was to determine longitudinal changes in muscle mass, muscle strength, and physical performance in acutely hospitalized older adults from admission up to 3 months post-discharge. Design: A prospective observational cohort study was conducted. Setting and Participants: This study included 401 participants aged !70 years who were acutely hospitalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…Overall, minimal changes in muscle quantity, quality or function were shown at the study population level. This is consistent with previous studies that have not shown significant change in handgrip strength in acutely admitted older adults during hospitalization, 15,16 or at 3 months post‐hospitalization 13 . A previous systematic review showed declines in handgrip strength in electively admitted older adults, but not in acutely admitted patients 16 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, minimal changes in muscle quantity, quality or function were shown at the study population level. This is consistent with previous studies that have not shown significant change in handgrip strength in acutely admitted older adults during hospitalization, 15,16 or at 3 months post‐hospitalization 13 . A previous systematic review showed declines in handgrip strength in electively admitted older adults, but not in acutely admitted patients 16 .…”
Section: Resultssupporting
confidence: 92%
“…A previous systematic review showed declines in handgrip strength in electively admitted older adults, but not in acutely admitted patients 16 . Conversely, muscle quantity has been shown to decline at 3 months post‐hospitalization, 13 but not during hospitalization, 14 and physical performance has actually been shown to improve in other studies 13,15 . This shows complexities in measuring dynamic changes in muscle quantity, quality and function in heterogeneous populations.…”
Section: Resultsmentioning
confidence: 98%
“…Decline in physical performance during hospitalization and up to 3 months post discharge has been attributable to loss of muscle mass and muscle strength, and exercise programs in the hospital and post discharge is crucial to reduce the impact of acute illness on physical performance and enhance recovery (21,49,50). Most studies have focused on high intensity resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of older adults who were followed up for 3 months after hospitalization, muscle strength and physical function recovered to the same level or even higher than that at the time of hospitalization. However, skeletal muscle mass did not recover during hospitalization (33) . Therefore, we believe that long-term nutritional physical therapy is necessary to improve skeletal muscle mass.…”
Section: The Effect Of Physical Therapy On Nutritionmentioning
confidence: 93%